The origins of common identity - Dehdari, Sirus H.,Gehring, Kai (CESifo, Center for Economic Studies & Ifo Institute, 2019)
The quasi-exogenous division of the French regions Alsace and Lorraine after the Franco- Prussian War allows us to provide evidence about group identity formation within historically homogeneous regions. We use several measures of stated and revealed preferences at the municipal-level in a geographical regression discontinuity design. More nation-state repression is associated with a strengthening of regional identity in the short, medium, and long run. We explain this in a model and document that the establishment of regionalist organizations is a key mechanism to strengthen identity. A relatively stronger regional compared to national identity is associated with preferences for more regional decision-making.
10419/214951
Keywords: Graue Literatur; group identity; nation-building; repression; assimilation; regional identity; borderregions; Alsace-Lorraine